Effect of underloads in small fatigue crack growth. (April 2022) - Field, I.; Kandare, E.; Dixon, B.; Tian, J.; Barter, S.
Graphical abstract: Highlights: Underloads cause the greatest acceleration in the small-crack regime. Possibility of both short and long-term effects of underloads. Evidence of an upper limit to the effectiveness of underloads. Occasional deceleration caused by underloads for long cracks. Abstract: There is considerable cost incurred within the aircraft industry due to the inability to accurately predict fatigue crack growth rates for complex loading scenarios. This is particularly the case for small cracks. This paper aims to facilitate the improvement of fatigue crack growth by investigating the effects of underloads on small cracks grown in the common airframe structural aluminium alloy; AA7050-T7451. Six novel loading spectra were used to quantify how underload spacing, magnitude, and consecutive application impact crack growth. Quantitative fractography of post-test fractures enabled crack growth measurements to be made at crack lengths as small as 100 µm. It was found that underloads accelerate growth rates most significantly for small cracks, though this effect appears to progressively diminish as the crack grows. The results also suggest that underloads may have both short and long-term effects on crack growth. This research paves the way for accounting for the acceleration of crack growth rates caused for small cracks in predictions, which if not considered, could lead to non-conservative fatigue life predictions. Ultimately, this should allow for more accurate growth rate prediction of high strength aluminium structures subject to underloads, as well as provide quantitative basis for future mechanistic studies.